A Study on Effect of Digital Practices on Sales Performance and Business Sustainability of Msmes (Journal of Informatics Education and Research, 2026)
The goal of this research is to better understand the relationship between sales performance and digital marketing's impact on a company's long-term viability. Structural equation modelling and other quantitative methods are employed for data analysis here. Choosing samples using methods that are most convenient for the researchers. In this study, we surveyed 142 micro, small, and medium enterprises (MSMEs) in the Bangalore area using online questionnaires and analyzed the responses. Data analysis reveals digital marketing had a positive and material effect on business outcomes including sales performance and long-term viability. Digital marketing can be executed over a wide range of channels, from social media and the web to search engine optimization (SEO). According to the findings, social media is a popular digital medium among MSMEs. This study analyzes data from both large and small companies to reveal the most successful sales strategies and approaches that can boost revenue and ensure a company's continued prosperity.